An Enrichment Method of Cell-free Fetal DNA from Mothers in the 11th Week of Pregnancy; On The Way of Non-invasive Prenatal Diagnosis of Beta-thalassemia as a Single Gene Disorder - E. Darabi; N. Ebadi; S. Mehrabi; A. Shakoori; M.R. Noori Daloii (Journal of Sciences, Islamic Republic of Iran)
The aim of this study was to examine the feasibility of using an economic and practical method in order to perform non-invasive prenatal testing of thalassemia as a sing gene disorder.Sixteen (16) pregnant mothers in the 11th week of pregnancy who were referred for prenatal diagnosis of thalassemia were selected. The parents had one of IVSII-1, IVSI-5 or FR codon 8/9 mutations. Enrichment of cffDNA was performed by a modified whole genome amplification. Based on the relative mutation dosage assay, wild and mutant alleles were compared by allele specific and Taqman allele specific real time PCR. The results obtained were compared with the results of invasive CVS. When both paternal and maternal mutations were identical IVSII-1 or FR codon 8/9, all three major thalassemic fetuses were detected by significant minus ∆Cts (Ct M-CtW) but no different ∆Cts was observed in seven cases in which fetuses were normal or carrier. In two cases with identical IVSI-5 parental mutations, the two major thalassemic fetuses could not be detected. In four cases with different paternal and maternal mutations, all three carrier fetuses were detected and in one major fetus, only paternal mutation was detected.This innovative method showed the detection of three of the five major thalassemic fetuses when the parental mutations were identical. Furthermore, paternal mutation inheritance could be determined in carrier or major thalassemic fetuses when the parental mutations were different. Further studies on fetuses in late gestational age may have more successful results.